Effectiveness of cognitive approach based on mindfulness of post-traumatic growth and sleep quality of breast cancer survivors - Zamani, Hatef; Bigdeli, Hossein; Tajeri, Biuok; Peymani, Javid (Applied Family Therapy Journal (AFTJ), 2021)
Aim: study was conducted with the aim of determining the effectiveness of cognitive approach based on mindfulness of post-traumatic growth and sleep quality of breast cancer survivors. Method: In a research of the type of experimental studies with a semi-experimental design, 30 women who recovered from breast cancer in Tehran were present and were assigned to two groups. Cognitive therapy based on mindfulness was implemented during 8 sessions on women suffering from cancer, but the control group did not receive any intervention. The data were collected through the post-traumatic growth questionnaire (Tadeschi and Calhoun, 1996) and sleep quality (Pitzborg, 1989) and They were analyzed using analysis of variance with repeated measurements and spss22 software. Results: The findings showed that there is a significant difference between the average of the two experimental and control groups in the variable of post-traumatic growth (F=45.34, P=0.001) and sleep quality (F=42.34, P=0.001), thus, cognitive therapy based on mindfulness on post-traumatic growth and Sleep quality has a significant effect (P